Khawalif in Explanation of Al-Marzouki (421 AH) to the Diwan of Hamasat Abu Tammam (231 AH) (Journal of the College of Basic Education, 2022)
My research, tagged with (khawalif in Al-Marzouk's Explanation of the Diwan Hamasa Abi Tmmam), deals with the study of Khawalif and followed it in Al-Marzouk's explanation of theDiwan of Hamasa because of its semantic importance in thearabic language in general and in thediwan of enthusiasm in particular. Theresearch deals with thereason for naming some grammatical topics as Khawalif and placing it in aseparate section under this name, and the way Al-Marzouki deals with them in this book (Poetry) Al-Marzouki dealt with in detail and explanation, the research sample is concerned with one of the explanations of the poetry of Abu Tammam's enthusiasm, which is composed of parts and a huge material. Themost important results are theemergence of most types of Khalefs in this explanation, as the research concluded that Al-Marzouki mentioned the most important purpose of the Khalefs, which is theexpression of all the Khalefs and their disclosure of theemotion and influence of their formulas, as theresearcher showed the originality and originality of theroots of this topic in this old text. Theresearcher recommends studying these modern topic and applying them to ancient texts to gain insight into therichness of our ancient heritage in these subjects